A influência da estratégia de suprimentos de uma grande empresa fabricante de elevadores sobre as estratégias de produção de dois fornecedores - Ueda, Rafael Maronezi (2013)
The Production Strategy has been the subject of several academic articles, with researches in different industries. On the other hand, Supply Strategy does not have references in a similar number and there is a gap to be filled. Furthermore, it is scarce the study of organizations in the same supply chain, and the influence between them. This study aims to describe and analyze the influence of a large elevator company's supply strategy on the production strategy of two of its suppliers, who designed 99% of its production to the customer company and the other with only 15 % of total volume. Through a case study, consisting of interviews conducted in the participating companies, it was found that the customer company´s Supply Strategy has greater influence on vendor's Production Strategy with higher production dedicated to it. This conclusion is taken by events such as the deployment of a new plant the city of the customer company, changes in engineering, plant layout, information systems and logistics of goods according to the customer needs. On the other hand, it was observed that the influence that the same company has over the other supplier is tenuous due to its low percentage of production that is destined to the customer company, and fact that the latter has a larger number of customers who must take account. Is worth nothing that the biggest influence does not necessarily translate into better performance in the short term, as in this study, the supplier with lower production percentage showed better performance compared to competing priorities, but the highest percentage, had to be more in line with customer needs following the same score in different priorities.